2015
DOI: 10.3892/ol.2015.3337
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation of CDH11 predicts a poor outcome for patients with bladder cancer

Abstract: Abstract. DNA methylation is one of the major mechanisms via which tumor suppressor gene inactivation occurs. For example, hypermethylation of the promoter region of cadherin 11 (CDH11), a novel tumor suppressor gene, frequently occurs in human cancer. In the current study, the methylation status of CDH11 was investigated in bladder cancer tissue samples, and the correlation with clinicopathological features and patient outcome was assessed. The methylation status of CDH11 was detected in 146 bladder cancer ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Multivariate analysis that the CDH11 promoter is hypermethylated in bladder cancer, melanoma and head and necktumors (31). The present study analyzed the methylation status of CDH11 in GC and normal gastric tissues.…”
Section: Univariate Analysismentioning
confidence: 89%
“…Multivariate analysis that the CDH11 promoter is hypermethylated in bladder cancer, melanoma and head and necktumors (31). The present study analyzed the methylation status of CDH11 in GC and normal gastric tissues.…”
Section: Univariate Analysismentioning
confidence: 89%
“…22e27 In particular, Cad-11 plays a role in epithelial-to-mesenchymal transition, which represents an inflammation-induced response that has a fundamental role in the progression from chronic inflammation to cancer. 28,29 Dysregulation of Cad-11 expression has been associated with many pathologic processes such as inflammation (eg, rheumatoid arthritis 18 ), fibrosis (eg, kidney, 30 pulmonary, 31 dermal 20 ), and cancer (eg, prostatic, 32 breast, 33 gastric, 34 bladder, 35 renal carcinoma, 34 and glioblastoma 36 ). Specifically, Cad-11 is a mesenchymal cadherin that is associated with more undifferentiated and aggressive cancer.…”
mentioning
confidence: 99%
“…Finally, all of the Portuguese studies were conducted by Dr. Carmen Jerónimo's group in IPO (Portuguese Oncology Institute) [32][33][34][35][36]. Regarding Asian studies, significant contributions have been made by Dr. Ying-Li Lin [37][38][39][40][41][42][43] at Jiangsu University and Dr. Liqun Zhou (especially in UTUC studies) [44][45][46]…”
Section: Resultsmentioning
confidence: 99%
“…The studies by Dr. Lin at JU have reported that methylation of CDH13 is associated with increased recurrence risk (p=0.0043), shorter time to progression (p=0.006), lower RFS (p<0.0001) [43] and with an increased risk of death (p=0.0071) [41]. In another of his studies, CDH11 methylation correlated with poor OS (p=0.0004) [40]. However, CDH13 methylation had no prognostic value in other cohorts [13,66].…”
Section: Cell-adhesionmentioning
confidence: 96%